Moderls of Internationzation of Two Argentine Pharmaceutical Companies in Historical Perspective: The Cases of Bagó and Sidus - Campins, Mónica (2015)
Internationalization is not a simple decision but rather a complex strategy that requires the presence of tangible and intangible resources that, in the case of a family firm, call for careful analysis. To understand this process, the present study reconstructs the historical trajectories of two important Argentine laboratories, Bagó and Sidus, in historical perspective, using the stage approach of the Uppsala school (U-model) and the perspective of resources and capacities (resource-based view). The findings suggest that internationalization took place in evolutionary stages, with prior construction of intangible assets on the local market.